2012
DOI: 10.1590/s1679-62252012000300015
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and genetic alterations in the freshwater neotropical fish Prochilodus lineatus after acute exposure to Microcystis aeruginosa

Abstract: Microcystins are secondary metabolites produced by different species of cyanobacteria, such as Microcystis aeruginosa (MA). In this study, the biochemical and genetic effects of lyophilized MA were evaluated in the neotropical fish Prochilodus lineatus exposed to 1 or 2 mg L -1 lyophilized MA (treated group) or only water (control group) in static toxicity tests for 24 and 96 h. The gills and liver were used in the analysis of biotransformation enzymes and antioxidant defenses, blood and gill cells in genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
4
5
0
Order By: Relevance
“…It is inferred that scavenging by toxin-induced antioxidant enzymes at early timepoints is sufficient to maintain hepatic redox balance, in accordance with other reports Garcia and Martinez, 2012).…”
Section: Oxidative Stress and Lipid Peroxidationsupporting
confidence: 91%
“…It is inferred that scavenging by toxin-induced antioxidant enzymes at early timepoints is sufficient to maintain hepatic redox balance, in accordance with other reports Garcia and Martinez, 2012).…”
Section: Oxidative Stress and Lipid Peroxidationsupporting
confidence: 91%
“…Recently, several studies have reported increased CAT and GPx activities in fish brain induced by atrazine, ethanol and other chemicals (Garcia and Martinez, 2012;Xing et al, 2012). We showed increased CAT and GPx activities in zebrafish brain induced by toxins, suggesting increased production of H 2 O 2 with accumulated toxicity, which is similar to previous studies (Correia et al, 2007;Garcia and Martinez, 2012).…”
Section: Cat and Gpx Activities In Aphantoxin-exposed Zebrafish Brainsupporting
confidence: 91%
“…Previous studies have demonstrated that many toxins or toxicants, such as cyanobacterial toxins, heavy metals and insecticides, can cause elevation of CAT and GPx activities in the liver, kidneys and gills of fish (Xu et al, 2009;Jin et al, 2010). Recently, several studies have reported increased CAT and GPx activities in fish brain induced by atrazine, ethanol and other chemicals (Garcia and Martinez, 2012;Xing et al, 2012). We showed increased CAT and GPx activities in zebrafish brain induced by toxins, suggesting increased production of H 2 O 2 with accumulated toxicity, which is similar to previous studies (Correia et al, 2007;Garcia and Martinez, 2012).…”
Section: Cat and Gpx Activities In Aphantoxin-exposed Zebrafish Brainmentioning
confidence: 99%
“…In addition to its ecological value, it is also economically important for the region (Cazenave et al, 2009). Several studies have demonstrated that this species is highly sensitive to different contaminants (Camargo et al, 2009;Modesto & Martinez, 2010;Garcia & Martinez, 2012;Santos & Martinez, 2012;Pereira et al, 2013), including petroleum derivatives (Simonato et al, 2006(Simonato et al, , 2008(Simonato et al, , 2011. All these features make the P. lineatus a suitable biological model for environmental monitoring.…”
Section: Introductionmentioning
confidence: 99%